(untitled) (Jurnal Riset Manajemen Akuntansi Indonesia, 2023)
This study uses descriptive qualitative research with 3 informants in this study, namely 1 Head of Administration, 1 Head of Community Empowerment and Development and 1 public service worker in Kramat Selatan Village, North Magelang District, Magelang City. To process and analyze the data, the author uses an interactive data model as proposed by Miles and Huberman. As a result, the factors that caused the performance of public service personnel in the Kramat Selatan Village, North Magelang District, Magelang City during the Covid-19 pandemic decreased, namely inadequate service facilities and infrastructure, there were still employees who needed to improve their competence and were also not proficient at using computers, people who needed services do not complete the required data, thus hampering the smooth running of services. Then the effort to improve the performance of public service personnel in the Kramat Selatan Village, North Magelang District, Magelang City during the Covid-19 pandemic is to provide adequate facilities as service facilities and infrastructure during this pandemic, improve performance by including training and capacity building in the computer sector. increasing socialization to the people of Kramat Selatan Village, North Magelang District regarding the procedures for public services and their requirements through various media.